KORELASI KONSEP SUNAT DALAM PERJANJIAN LAMA DENGAN BUDAYA SUNAT DI MASYARAKAT NIAS - Steven Anugerah Jaya Ndruru; Firman Panjaitan (Misioner, 2021)
In the Old Testament, circumcision was seen as a major part of establishing oneself as part of God's people. In the adoption of Israel as God's people at Sinai, every Israelite must be circumcised. It is based on God's command to Abraham, as a sign of the covenant. But actually the culture of circumcision is not a typical Israeli culture, but is a culture that is common in the Middle East, the only thing that distinguishes the culture of Israeli circumcision from the Middle East is in God's decree in the covenant that raised Israel (a descendant of Abraham) as God's people. So there is a spiritual meaning in the cultural content of circumcision in the Old Testament for the Israelites. It turns out that the spiritual understanding of circumcision is not only owned by Israel, because this is also owned by the Nias Tribe. By using qualitative research methods, which are complemented by a literature study approach, this research results in an understanding that the culture of circumcision for the Nias tribe is a culture that signifies them as God's people. So that circumcision is an absolute for every Nias community.